(untitled) (Journal of Dhaka Medical College, 2016)
Acute myeloid leukemia (AML) is a clonal, malignant disease of hematopoietic tissue.Main variables precluding cure are the treatment-related mortality and relapse rates.The most common induction chemotherapy regimens in AML involve the use of cytarabine (Ara-C) and an anthracycline. It was observational study carried out in the inpatient Department of Hematology, Dhaka Medical College Hospital, Dhaka, from July 2009 to June 2014.76 newly diagnosed cases of AML patients between 15 year to 60 yearwere enrolled in this study. All patient received standard induction therapy with Daunorubicin 45mg/m2 I/V for 3 days and Ara-C 100mg/m2 I/V over 24 hours for 7 days. A bone marrow aspirate to assess remission status was carried out at day 28+, after the peripheral recovery.The mean age of the patients were 35.12±12.45 years, ranging from 17 to 55 years. 68% were male and 32% cases were female. Total 34(44.7%) patient achieved complete remission (CR), out of them 17% had t(8:21), 5.8% had inv16 and only 2.9% was FLT3 positive. 26(34%) patient achieved partial remission (PR), 11% had t(8:21) and 3.8% inv16. 13.1% patient failed to achieve any remission (Non responder, NR) and 6 patient (7.8%) died during induction therapy. Age, performance status and cytogenetics had significant influence (P<0.025, P<0.030 and P<0.003 respectively) on the outcome. The presenting peripheral blast percent (%) also had a significant influence (P=0.012) on the outcome after induction therapy.Complete remission rate is significantly lower in our center comparing discussed study. This is probably due to lack of modern hospital facility and socio-economic condition of our patients.Cytogenetic analysis provides the most powerful independent predictor of disease outcome. To improve outcome, all the supportive measures have to be improved and more tools are required in identifying the good prognostic groups. J Dhaka Medical College, Vol. 24, No.2, October, 2015, Page 141-145